Beam-Column Timber Joint Connection Behavior Due to Nail and Modified-Washer Reinforcement Tests - Yosafat Aji Pranata; Anang Kristianto; Olga Pattipawaej (Masyarakat Peneliti Kayu Indonesia, 2019)
Timber connection capacity, in case of beam-column joint connection provides significant impact on the wooden building structures. Strength and stiffness of timber connections using reinforcement technique of wooden building structures have not been studied intensively. This paper studies the use of nails and modified-washer to improve wood connection’s performance. The experimental tests were conducted in the laboratory by comparing the partial connection between test specimen timber without reinforcement (standard type) and the reinforcement (PRP type). The testing was conducted based on partial connection beam-column joint test using Universal Testing Machine’s with a modified holder. Wood studied includes Meranti (Shorea spp.) and Mersawa (Anisoptera spp.). PRP type connection was using nails and modified-washer strengthening, and standard type connection was using a classic washer. Parameters studied were strength and stiffness of the connection, reviewed both: proportional limit load and ultimate limit load conditions. Result obtained from this research indicates that the use of nails and modified-washer make a positive contribution to improving the performance of the beam- column timber joint connections, in terms of strength capacity (both of proportional limit and ultimate limit loads) and stiffness capacity (displacement ductility ratio). Meranti beam-column timber joint is more brittle than Mersawa beam column timber joint, it has an impact on the results. PRP-type of Mersawa timber connection produces a higher ductility than the standard type, while the PRP-type of Meranti timber connection produces a similar ductility to the standard type.